Atrial Fibrillation Is an Independent Predictor of Mortality in Critically Ill Patients*. Issue 10 (October 2015) - Shaver, Ciara M.; Chen, Wei; Janz, David R.; May, Addison K.; Darbar, Dawood; Bernard, Gordon R.; Bastarache, Julie A.; Ware, Lorraine B.
<x xml:space="preserve">Abstract</x> Objectives: Atrial fibrillation has been associated with increased mortality in critically ill patients. We sought to determine whether atrial fibrillation in the ICU is an independent risk factor for death. A secondary objective was to determine if patients with new-onset atrial fibrillation have different risk factors or outcomes compared with patients with a previous history of atrial fibrillation. Design: Prospective observational cohort study. Setting: Medical and general surgical ICUs in a tertiary academic medical center. Patients: One thousand seven hundred seventy critically ill patients requiring at least 2 days in the ICU. Interventions: None. Measurements and Main Results: Demographics, medical history, development of atrial fibrillation, fluid balance, echocardiographic findings, medication administration, and hospital mortality were collected during the first 4 days of ICU admission. Atrial fibrillation occurred in 236 patients (13%) (Any AF). Of these, 123 patients (7%) had no prior atrial fibrillation (New-onset AF) while the remaining 113 (6%) had recurrent atrial fibrillation (Recurrent AF). Any AF was associated with male gender, Caucasian race, increased age, cardiac disease, organ failures, and disease severity. Patients with Any AF had increased mortality compared with those without atrial fibrillation (31% vs 17%; p < 0.001), and Any AF was independently associated with death (odds ratio, 1.62; 95% CI, 1.14–2.29; p = 0.007) in multivariable analysis controlling for severity of illness and other confounders. The association of atrial fibrillation with death was magnified in patients without sepsis (odds ratio, 2.92; 95% CI, 1.52–5.60; p = 0.001). Treatment for atrial fibrillation had no effect on hospital mortality. New-onset AF and Recurrent AF were each associated with increased mortality. New-onset AF, but not Recurrent AF, was associated with increased diastolic dysfunction and vasopressor use and a greater cumulative positive fluid balance. Conclusions: Atrial fibrillation in critical illness, whether new-onset or recurrent, is independently associated with increased hospital mortality, especially in patients without sepsis.